Synthesis and Characterization of New Thiazine Compounds Derivatized From 1-(Pyrazin-2-Yl)-3-(Benzylidene) Propanone and Study of Their Biological Effectiveness - Saad Salim Jasim; Shakhawan Beebany; Jawdat Hilmi Abdulwahid; Khalid A. Al-Badrani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study examines the synthesis and characterization of new compounds produced from chalcone, confirming their favorable yield and excellent purity utilizing Using FT-IR and 1H and 13C NMR spectroscopy. The compounds showed efficacy comparable to that of conventional antibiotics, demonstrating substantial bactericidal activity against Staphylococcus aureus and Escherichia coli. Interestingly, molecule S10 had stronger antibacterial activity, possibly as a result of its efficient electronic pairings. Furthermore, the compounds demonstrated resilience for up to 45 seconds when tested for stability under helium-neon laser irradiation. Longer exposure (60 seconds), however, caused discernible color and melting point alterations, suggesting thermal or photochemical deterioration. These results point to the possibility of additional pharmacological uses for molecules produced from chalcone.